Language Multicultural Education in the Ethno-Regional Context - Anzhelina A. Koriakina (ÜNİVERSİTEPARK Limited, 2018)
The article is focused on the problem of language multicultural education in the ethno-regional context. The content of the problem is revealed through its constituent concepts "multicultural education" and "language multicultural education". Language multicultural education in the ethno-regional context is considered as a process of acquiring knowledge about ethno-cultural diversity of the co-studied languages countries and the relationships between cultures in the modern multicultural world through polylogue of cultures. It is revealed that language multicultural education in the ethno-regional context is characterized by a number of features: polylogue of three linguocultures at the regional, state and global levels; equal polylogue of cultures, built on mutual respect of cultures involved in contact; ethno-cultural component focused on formation of a representative of a particular ethnic group and multicultural component, whose purpose is creation of a person of universal culture.